Pemberdayaan Penenun Tenun Ikat Kabupaten Timor Tengah Selatan Berbasis Ekonomi Kreatif dan Budaya Lokal - Arie Lebo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
This community service was carried out in South Central Timor Regency to empower ikat weavers to develop a creative economy based on local culture. The selection of this topic is motivated by the sub-optimal utilization of ikat weaving's potential as a productive economic activity due to limitations in weavers' knowledge, skills, and market access. The service activity was carried out using a participatory empowerment approach, which positions the weavers as active subjects at every stage. The methods used include socialization, capacity-building assistance in knowledge and skills, and strengthening the understanding of product diversification and the economic value of ikat weaving. The results of the activity show an increase in weavers' knowledge and skills, a change in attitude toward weaving as a productive economic endeavor, and the emergence of a diverse range of ikat weaving products. Although the increase in revenue has not been significant in the short term, this activity has an initial impact on strengthening motivation, group cooperation, and marketing development opportunities. The results of this service are important as a basis for developing sustainable, locally based weaver empowerment programs.